Consumer Protection Against Exoneration Clauses in Laundry Service Notes in Samarinda City - Arifah, Salsabila Budi; Susanti, Erna; Damanik, Amsari (LEGAL BRIEF, 2024)
The exoneration clause is a clause that limits or eliminates responsibilities that should be borne by business actors. This clause is often found in laundry service notes in Samarinda City, even though its application is prohibited in Article 18 of Law Number 8 of 1999 concerning Consumer Protection. This research uses a social-legal approach to analyze the application of exoneration clauses and the implementation of consumer protection regarding the use of exoneration clauses in laundry service notes in Samarinda City. The research results show that the use of exoneration clauses in laundry service notes is detrimental to consumers because consumers do not receive compensation. The less than optimal role of the Consumer Dispute Resolution Agency (BPSK) causes the public, both consumers and business actors, to lack understanding of their rights and obligations. Therefore, there is a need for deeper attention to the application of exoneration clauses so that consumers are protected.